Airline Logistics AI Performance Framework A 360-Degree, Multi-Layered KPI Approach for Safety, Sustainability, Efficiency, and Innovation - MoghadasNian, SeyyedAbdolHojjat; Moslem Mahmoudi (20th Iranian International Industrial Engineering Conference, 2025)
The integration of Artificial Intelligence (AI) in airline logistics is a transformative force, enhancing operational efficiency, safety, sustainability, and innovation. This paper introduces a 360-degree, multi-layered Key Performance Indicator (KPI) framework designed to assess and optimize AI performance within the airline logistics sector. The framework addresses key dimensions such as safety, sustainability, operational efficiency, and ethical AI, providing a comprehensive tool for evaluating AI systems’ contributions to airline operations. By offering insights into AI integration challenges and the importance of strategic alignment, the proposed framework serves as a valuable resource for airline managers, regulators, and technology providers in fostering continuous improvement, regulatory compliance, and innovation in the logistics ecosystem.